Outcomes of Single Suture Mueller's Muscle Conjunctival Resection: Ethnic Considerations. Issue 1 (4th June 2021) - Gur, Zvi; Chang, Minwook; Liu, Catherine Y.; Korn, Bobby S.; Kikkawa, Don O.
Abstract : Purpose: To compare outcomes of Mueller's Muscle Conjunctival Resection (MMCR) between 2 groups of patients with different anatomy due to ethnic heritage. Methods: The medical records of patients who underwent MMCR between 2013 and 2018 were retrospectively reviewed. Patients who underwent additional procedures, such as upper blepharoplasty and browplasty, were excluded from the study. Patients were divided in 2 groups based on self-identified ethnic groups (Asian and Caucasian). Image J software was used to calculate MRD1 from digital images. The improvement of MRD1 (net MRD1) after surgery was evaluated and compared between 2 groups. Results: Eighty-three eyes of 68 patients were included in this study. The Asian group consisted of 41 eyelids from 28 patients. The Caucasian group consisted of 42 eyelids from 40 patients. The average age was 52.18 (SD 20.176) in the Asian group compared with the 66.45 years (SD 9.22, p  < 0.005) in the Caucasian group. The mean improvement of MRD1 was 1.96 ± 0.75 mm in Asian group and 2.05 ± 0.72 mm in Caucasian group, which was not statistically significant ( p  = 0.62). The incidence of ptosis overcorrection and undercorrection between the groups was also not statistically significant. Conclusions: There was no statistically significant difference in the surgical outcomes among the 2 study groups. Despite differences in the anatomy of Caucasian and Asian eyelids, MMCR is a successful procedure in patients self-identified from both ethnic groups. Abstract : Despite significant changes in eyelid anatomy and appearance among different ethnic groups, Mueller's muscle conjunctival resection is a successful procedure with equal efficacy in Asian and Caucasian populations.